2, 2‐Difluoro‐1, 3‐diketones as gem‐Difluoroenolate Precusors for Asymmetric Aldol Addition with N‐Benzylisatins. Issue 17 (4th August 2016) - Qian, Jinlong; Yi, Wenbin; Huang, Xin; Jasinski, Jerry P.; Zhang, Wei
Abstract: 2, 2‐Difluoro‐1, 3‐diketones are introduced as gem ‐difluoroenolate precursors for the first example of an organocatalytic asymmetric aldol addition with N ‐benzylisatins to form 3‐difluoroalkyl‐3‐hydroxyoxindoles. Abstract :